Sumpit (Blowgun) as Traditional Weapons with Dayak High Protection - Hamid Darmadi (JETL (Journal of Education, Teaching and Learning), 2018)
The Dayak ancestors who live amid lush forests with towering tree trees and inhabited by a variety of wild animals and wild animals, inspire for the Dayak's ancestors to make weapons that not only protect themselves from the ferocity of forest life but also have been able to sustain the existence of their survival. Such living conditions have motivated the Dayak ancestors to make weapons called "blowgun" Blowgun as weapons equipped with blowgun called damak. Damak made of bamboo, stick and the like are tapered and given sharp-sharp so that after the target is left in the victim's body. In its use damak smeared with poison. Poison blowgun smeared on the damak where the ingredients used are very dangerous, a little scratched it can cause death. Poison blowgun can be made from a combination of various sap of a particular tree and can also be made from animals. Along with the development of blowgun, era began to be abandoned by Dayak young people. To avoid the typical weapons of this high-end Dayak blowgun from extinction, need to be socialized especially to the young generation and to Dayak young generation especially in order, not to extinction.